Mechanism-Based Explanations in the Impact Evaluation of Public Interventions: Digging Deeper into Why and How Programmes Worked or Failed to Work - Kubera, Paulina (Journal of Public Governance, 2022)
Objectives:The aim of the article is to consider the evaluation of public interventions through the prism of evidencebased policy (EBP) as well as, more specifically, its potential to address the problem of how to produce in the process of impact evaluation usable knowledge that can help improve policymaking and policy implementation which can be accumulated over time, where evaluations will not be single endeavours and one-off studies, but will contribute to the growing body of knowledge. Research Design & Methods:The article provides a critical overview of the research literature on evaluation approaches and methods as tools for gathering and apprising evidence relevant for policymaking and policy implementation. Findings:Building upon the identified limitations of the traditional input/output approach to impact evaluation of public interventions, alternative approaches to evaluation are considered that make use of a theory that properly explicates the causal mechanisms linking programme activities with programme outcomes, confronting the mechanisms with empirical observations. As a strategy for synthesising the gained knowledge, the realist synthesis is considered as being more appropriate for reviewing research on complex social interventions (rather than traditional meta-analysis). Implications / Recommendations:The article demonstrates how theory-based evaluation with mechanistic explanation and realist synthesis can contribute to growing evidence for policy needs, identifying also their limitations and practical problems related to their implementation. Contribution / Value Added:The article contributes to the existing pool of knowledge by providing important insights into how to use mechanism-based explanations in impact evaluation to make stronger causal claims and enhance policy-learning.